1976
DOI: 10.1093/oxfordjournals.aje.a112226
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Rubber Workers I. White Male Union Employees in Akron, Ohio

Abstract: Mortality among a cohort of 13,571 white male rubber workers in Akron, Ohio is described. Mortality from all causes was 82% of that expected on the basis of death rates for US white males. Excess deaths from cancer (observed/expected numbers) in specific sites among workers in specific work areas include stomach:processing (18/9.9); large intestine: processing (14/10.5); lung: tire curing (20/12.4): bladder: all workers (48/39.5); brain: tire building (7/3.7): lymphatic: tire building (11/7.1): and leukemia: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The mortality experience of approximately 25,000 past and current employees from one plant in Ohio going back to 1925 has been reviewed by Monson and Nakano (1,2 …”
Section: Mortality Studiesmentioning
confidence: 99%
“…The mortality experience of approximately 25,000 past and current employees from one plant in Ohio going back to 1925 has been reviewed by Monson and Nakano (1,2 …”
Section: Mortality Studiesmentioning
confidence: 99%
“…Several previous studies of rubbers workers [Fox et al, 1974;Fox and Collier, 1976;McMichael et al, 1976a;Monson and Nakano, 1976;Mancuso, 19741 reported increased lung cancer risks among workers engaged in the compounding and mixing of raw rubber stocks and in the curing of green rubber products. The results of the present study do not support these findings.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…NMOR probably arises as a trace con taminant in bismorpholinecarbamylsulfenamide, which is used as an accelerator. It is of interest to note that several recent studies agree that lung and gastrointesti nal cancers occur at increased risk among workers in several of these same areas [Monson and Fine, 1978;Monson and Nakano, 1976;Mancuso, 1976 et al., 1976;McMichael et al, 1976;Andjelkovich et al, 1977], However, at this point further speculation on the possible involvement of N-nitroso compounds in the etiology of rubber worker cancer is premature. We know of two US epidemiology studies which are planning to investigate the nitrosamine-rubber worker link.…”
Section: Workplace Exposure To Airborne N-nitrosaminesmentioning
confidence: 99%